Selective Enrichment of Fibrous Fragments Formed from Milled Carbon Fibers by Means of Gravitational Settling in a Liquid - Nicolas Rodriguez y Fischer; Kerstin Kämpf; Torben Peters; Nico Dziurowitz; Carmen Thim; Daniela Wenzlaff; Asmus Meyer-Plath; Daphne Bäger (Fibers)
The aim to reduce health risks of workers related to inhalative exposure to potentially toxic dusts requires the selection of appropriate measures depending on the hazard classification of the dust-composing materials. Due to their biodurability, respirable carbon fibers and their fragments can impose such health risks but are currently lacking hazard classification. Here, a method is presented for fragmenting carbon fiber materials and enriching fibrous fragments to a level that is expected to allow differentiating between fiber and particle overload-related toxic effects. The method was applied to a commercial polyacrylonitrile-based carbon fiber. It was ground in an oscillating ball mill, homogenized in a liquid using ultrasonication and left undisturbed for gravitational settling. This way, a vertical gradient in particle size and shape formed, from which the supernatant was collected. Fragment morphologies were characterized with large ensemble statistics by semi-automated evaluation of scanning electron microscopy images employing an artificial neural network for binary semantic segmentation. The number of fibrous fragments of respirable and thus critical fiber morphology was increased from <semantics>0.36×106</semantics> to <semantics>6×106</semantics> WHO-analog fibers per mg. This corresponds to a factor of about 15 compared to the initial ground material. Since the mass percentage of non-fibrous objects was also significantly reduced, the requirements for a subsequently scheduled toxicological study with intraperitoneal application were fulfilled. Intraperitoneal testing is an accepted method for assessing the carcinogenic potential of biopersistent fibers. The developed method allows enriching fibrous fractions of concern at acceptable throughput and enables testing fiber toxicological effects of respirable fragments from disintegrated polyacrylonitrile-based carbon fibers.